2020
DOI: 10.1002/advs.202000609
|View full text |Cite
|
Sign up to set email alerts
|

A Designed α‐GalCer Analog Promotes Considerable Th1 Cytokine Response by Activating the CD1d‐iNKT Axis and CD11b‐Positive Monocytes/Macrophages

Abstract: Selective helper T cell 1 (Th1) priming agonists are a promising area of investigation for immunotherapeutic treatment of various diseases. α ‐galactosylceramide ( α ‐GalCer, KRN7000), a well‐studied Th1‐polarizer, simultaneously induces helper T cell 2 (Th2)‐type responses, which is a major drawback for its clinical applications. Based on surflex‐docking computation, α ‐GalCer‐diol, with added hydroxyl groups in the acyl chain, is designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…( 29 )reported that threitolceramide- (ThrCer-) induced activation of NKT cells. In addition, researchers have managed to createα-GalCer analogues artificially, including α-GalCer-diol (with added hydroxyl groups in the acyl chain compared to α-GalCer, Juan Ma et al., 2020) ( 30 )and6′-modified α-GalCer analogues (Matthias Trappeniers et al., 2008) ( 31 ). Hopefully, with careful design, these analogues will be applicable as preventative and therapeutic vaccine adjuvants ( 32 , 33 ).…”
Section: Nkt-cell Activatorsmentioning
confidence: 99%
“…( 29 )reported that threitolceramide- (ThrCer-) induced activation of NKT cells. In addition, researchers have managed to createα-GalCer analogues artificially, including α-GalCer-diol (with added hydroxyl groups in the acyl chain compared to α-GalCer, Juan Ma et al., 2020) ( 30 )and6′-modified α-GalCer analogues (Matthias Trappeniers et al., 2008) ( 31 ). Hopefully, with careful design, these analogues will be applicable as preventative and therapeutic vaccine adjuvants ( 32 , 33 ).…”
Section: Nkt-cell Activatorsmentioning
confidence: 99%
“…The mode of action of α-Galcer is largely due to its strong binding to differentiated clusters (CD1d), members of the CD1 family that express glycoproteins on the plasma membrane of antigen-presenting cells (APCs), such as dendritic cells (DCs). When the α-Galcer-CD1d complex is presented to the semi-invariant T cell receptor (TCR) on immutable natural killer T cells (iNKTs), a ternary complex is formed, leading to the secretion of various cytokines [122]. More recently, Sainz et al combined the NKT agonist α-GalCer, melanoma-associated peptide antigens as well as TLR ligands CpG and MPLA with nanoparticles, which promoted DC maturation, consequently leading to the up-regulation of co-stimulatory markers, such as CD80/CD86, and the production of IL-12/CCL17.…”
Section: Tlr4a + Tlr9amentioning
confidence: 99%
“…to the secretion of various cytokines [122]. More recently, Sainz et al combined the NKT agonist α-GalCer, melanoma-associated peptide antigens as well as TLR ligands CpG and MPLA with nanoparticles, which promoted DC maturation, consequently leading to the up-regulation of co-stimulatory markers, such as CD80/CD86, and the production of IL-12/CCL17.…”
Section: Tlr4a + Tlr7/8amentioning
confidence: 99%
“…Antigen peptide-MHCII complex presented by professional antigen presenting cells (APCs) including DCs, macrophages and B cells is essential for the activation of Th1 cells [23][24][25]. The above correlation and enrichment analyses identi ed that IGSF6 was strongly linked with MHCII complex and might participate in antigen uptake by macrophages and DCs through acting as a co-receptor.…”
Section: Igsf6 Expression Is Positively Correlated With the Antitumor...mentioning
confidence: 99%